Estudio comparativo en las seguridades de los equipos de Red Microtik y cisco en la institución pública del GAD Municipal San Francisco de Puebloviejo. - Fajardo Rosales, Betsy Jacqueline (2023)
In the world of computing, security is one of the main concerns for network administrators. The security of network equipment is an essential factor to ensure the integrity of computer systems. In this sense, there are two of the main providers of network equipment: MikroTik and Cisco. MikroTik is a provider of network hardware and software. It offers a variety of routers, switches, and other network devices. MikroTik devices are used to provide connectivity and security services in small and enterprise networks. Cisco is a leading provider of network devices. It offers a full range of network equipment, including routers, switches, firewalls, and security equipment. These devices are used to provide connectivity and security in networks. In this comparative study, the security of the network equipment of these two main providers will be analyzed. The different levels of security offered by MikroTik and Cisco network equipment will be evaluated. The quality of the security products and services offered by both vendors will be examined. Finally, we will discuss how these securities compare with modern security requirements. The comparative study on the security of MicroTik and Cisco network equipment is a comprehensive analysis of the different security aspects of these network devices. This includes the analysis of the security protocols of each device, as well as the evaluation of how the devices behave when exposed to external attacks. The purpose of this study is to better understand how these network devices provide security to the networks in which they are integrated, and to identify any weaknesses in the security of each device. This will allow network administrators to implement better security measures in their networks to prevent external attacks and maintain data integrity.